Penetration rate prediction for percussive drilling with rotary in very hard rock - Hung, Nguyen Van; L. Gerbaud; R. Souchal; C. Urbanczyk; Fouchard, C. (Vietnam Journal of Science and Technology, 2016)
This paper is the following part of our project to predict the penetration rate for percussive drilling with rotary in very hard rock. As results in [1] have been shown that the rate of penetration was strong influent by Brazilian tensile strength and it was exist the correlation between the rate of penetration and the rock properties. Yet, the study was valid on six hard rocks in experimental result of test tricone and rotary with percussive. All relationships have been shown but the coefficient R2 is still very low. This paper will present a new relationship with high value of R2 based on previous data and also establish a mathematical relationship, numerical model to predict the penetration rate.